Gradient-structure magnesium-aluminum-zirconium composite refractory material and preparation method thereof

By designing gradient structures, dense outer layer and porous inner zones in refractory materials, combined with oxidation and nitriding reactions during high-temperature sintering, the problem of difficult to take into account both the erosion and thermal shock resistance is solved, and efficient performance improvement and service life extension are achieved.

CN119569437APending Publication Date: 2025-03-07UNIV OF SCI & TECH BEIJING +1

Patent Information

Application Number
CN202411683773.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing refractory materials are difficult to take into account both the resistance to erosion and thermal shock resistance, resulting in the problems of cracks and performance degradation when used in high-temperature environments.

Method used

The gradient structure is designed with a dense MgAl2O4-Al2O3-ZrO2 composite material on the outer layer and a porous Al2Zr3C4-MgAlON-enhanced MgAl2O4 composite material on the inside. Through the oxidation and nitriding reactions during the high-temperature sintering process, a magnesium-aluminum-zirconium composite refractory material with functional gradient characteristics is formed.

Benefits of technology

The high corrosion resistance and thermal shock resistance of the material are achieved synergistically, and the stability and strength can be maintained in high-temperature environments and prolong service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569437A_ABST
    Figure CN119569437A_ABST
Patent Text Reader

Abstract

The invention relates to a magnesium-aluminum-zirconium composite refractory material with a gradient structure and a preparation method thereof, and belongs to the technical field of refractory materials. The magnesium-aluminum-zirconium composite refractory material with the gradient structure is prepared from the following raw materials in percentage by mass: 70 to 95 percent of magnesium aluminate spinel and 5 to 28 percent of aluminum-zirconium alloy. The preparation method comprises the following steps: weighing magnesium aluminate spinel and an aluminum-zirconium alloy raw material according to a ratio, adding 2-5% of a phenolic resin binder, fully and uniformly mixing, carrying out compression molding, placing a green body in a tunnel kiln, drying at 150-200 DEG C for 12-24 hours, and carrying out high-temperature sintering at 1350-1750 DEG C in an air atmosphere for 3-8 hours. According to the invention, a gradient functional structure is constructed by utilizing the sensitive characteristic of aluminum-zirconium alloy to oxygen partial pressure at high temperature; a MgAl2O4-Al2O3-ZrO2 composite compact layer is synthesized in situ on the surface of a product with high oxygen partial pressure, so that the erosion resistance of the material can be effectively improved; al2Zr3C4 and MgAlON reinforced phases are synthesized in situ in the interior with low oxygen partial pressure, so that the strength and thermal shock resistance of the material can be effectively improved. The material provided by the invention has excellent erosion resistance, thermal shock resistance and high mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a gradient structure magnesium-aluminum-zirconium composite refractory material and a preparation method thereof. Background Art

[0002] Refractory materials are important foundation and supporting materials for high-temperature industries. During high-temperature service, refractory materials are subjected to severe thermal shock, chemical erosion by complex media, and mechanical wear, etc., and must take into account excellent thermal shock resistance, erosion resistance, and high mechanical strength. However, the key service properties of refractory materials often restrict each other. For example, excellent erosion resistance requires a dense structure, but this will sacrifice the thermal shock resistance of the material; excellent thermal shock resistance requires a certain amount of pores to relieve thermal stress, but this will reduce the strength of the material and may aggravate the penetration and erosion of the medium into the material. According to the different service microenvironments of different areas such as the cold and hot surfaces of refractory products, composite material composition and gradient structure design are carried out to achieve zoning enhancement of key service performance, which is an important direction for the development of high-performance, long-life and functional advanced refractory materials. Taking refractory products such as continuous casting ladle slides and RH refining furnace linings as examples, their hot surfaces are directly subjected to the scouring and erosion of high-temperature molten steel, requiring them to have excellent scouring and erosion resistance; while the temperature difference between the cold and hot surfaces is extremely large, and the stress distribution is uneven, so the thermal shock resistance inside the product is particularly important. The development of new refractory materials with functional gradient characteristics of "high corrosion resistance working layer-thermal shock resistance internal zone" through material composition composite and structural gradient design has become a current research hotspot.

[0003] Magnesium-aluminum spinel has excellent high-temperature performance and is an important oxide refractory material, but its corrosion resistance is poor. Studies have shown that the introduction of ZrO2 into magnesium-aluminum spinel materials can significantly improve the mechanical properties and corrosion resistance of MgAl2O4, because ZrO2 can react with CaO, the main chemical component in the slag, to form a high melting point phase CaZrO3, forming a dense layer to prevent further penetration of the slag. The Chinese patent (application number: CN202311775105.X) "A MgO-Al2O3-ZrO2 refractory brick and its preparation method" discloses a new type of MgO-Al2O3-ZrO2 refractory brick for non-ferrous metal smelting furnaces with highly dispersed ZrO2 and MgAl2O4, which has excellent corrosion resistance and high-temperature mechanical properties, is suitable for non-ferrous metal smelting and steel smelting refractory products, and can greatly improve the life of non-ferrous metal smelting furnaces and RH refining furnaces. However, since the system is a pure oxide system with low thermal conductivity, its thermal shock resistance still has a lot of room for improvement. Especially for large-sized refractory products used for linings of RH refining furnaces, non-ferrous metal smelting furnaces, etc., there is a large temperature gradient inside, which leads to stress concentration and easily causes cracks. Therefore, the thermal shock resistance inside the product is the key factor determining its service life.

[0004] In terms of material composition, non-oxide Al2Zr3C4 and MgAlON have high thermal conductivity, low thermal expansion coefficient, and excellent thermal shock resistance; in terms of material structure, the porous structure can effectively alleviate stress concentration. Therefore, in-situ synthesis of Al2Zr3C4 and MgAlON reinforcement phases in the oxide matrix to form a strong ceramic bond can significantly improve the high-temperature mechanical properties of the material on the one hand, and significantly improve the thermal shock resistance of the material on the other hand. However, how to integrate MgO-Al2O3-ZrO2 materials with good corrosion resistance and Al2Zr3C4-MgAlON-MgAl2O4 materials with good thermal shock resistance to prepare high-performance functional gradient materials has not been reported. Summary of the invention

[0005] In order to overcome the bottleneck of the existing technology that it is difficult to balance the corrosion resistance and thermal shock resistance, the present invention proposes to utilize the sensitive characteristics of aluminum-zirconium alloy to oxygen partial pressure at high temperature, design in-situ synthesis, cascade reaction path ("passive oxidation" → "active oxidation" → "direct nitridation / carbonization"), and prepare a new type of gradient structure magnesium-aluminum-zirconium composite refractory material, whose outer layer is a dense MgAl2O4-Al2O3-ZrO2 composite material, which can effectively improve the corrosion resistance of the material; its interior is a porous Al2Zr3C4-MgAlON reinforced MgAl2O4 composite material, which can effectively improve the thermal shock resistance of the material. The new type of refractory material with the functional gradient characteristics of "high corrosion resistance working layer-thermal shock resistance internal zone" has broad application prospects in non-ferrous metal smelting furnaces and RH refining furnaces.

[0006] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows:

[0007] A gradient structured magnesium-aluminum-zirconium composite refractory material, characterized in that its outer layer is a dense MgAl2O4-Al2O3-ZrO2 composite material with a thickness of 0.1 to 5 mm and a porosity of ≤5%, and its inner layer is a MgAl2O4-MgAlON-Al2Zr3C4-AlZr composite material with a porosity of 10% to 20%.

[0008] Furthermore, the gradient structured magnesium-aluminum-zirconium composite refractory material comprises the following raw material compositions in percentage by mass: 70% to 95% magnesium-aluminum spinel, 5% to 30% zirconium-aluminum alloy, and 2% to 5% phenolic resin binder.

[0009] Furthermore, the magnesia-alumina spinel raw material includes aggregates with a particle size of 3-1mm and <1mm and fine powder with a particle size of ≤0.08mm, wherein the mass percentage of the magnesia-alumina spinel aggregates with a particle size of 3-1mm and <1mm is 65%-90%, and the mass percentage of the magnesia-alumina spinel fine powder is 5-30%; the zirconium-aluminum alloy raw material is a fine powder with a particle size of ≤0.1mm.

[0010] Preferably, the main chemical components of the zirconium-aluminum alloy raw material are Ti and Al elements. In terms of mass percentage, the content of Zr element is 10% to 50%, and the content of Al element is 50% to 90%.

[0011] The preparation method of the gradient structure magnesium aluminum zirconium composite refractory material comprises the following steps:

[0012] (1) weighing magnesium-aluminum spinel, zirconium-aluminum alloy, and binder according to a ratio, stirring evenly, and making a slurry;

[0013] (2) placing the clay material in step (1) in a press to form a green body;

[0014] (3) placing the green body in step (2) in a tunnel kiln and drying it at 150° C. to 200° C. for 12 to 24 hours to reduce the residual moisture to less than 1.5%;

[0015] (4) The dried bricks are placed in a tunnel kiln and fired at 1350°C to 1750°C in an air atmosphere for 3 to 8 hours.

[0016] Principle of the present invention: During the high-temperature firing process, the oxygen partial pressure of the outer layer of the brick is relatively high, and the aluminum-zirconium alloy in the composite material preferentially undergoes a passive oxidation reaction, formula (1), and Al2O3 and ZrO2 are generated in situ. On the one hand, the reaction is accompanied by volume expansion, and the reaction products Al2O3 and ZrO2 fill in the pores to promote densification; on the other hand, the newly generated Al2O3 and ZrO2 have strong reaction activity and further dissolve in the magnesium-aluminum spinel at high temperature, formula (2), to generate the MAZ ternary metastable phase, which decomposes during the cooling process to produce the MgAl2O4-Al2O3-ZrO2 eutectic, thereby achieving a highly uniform and fine dispersion of the ZrO2 phase and giving full play to the anti-corrosion performance of the ZrO2 phase.

[0017] AlZr + O2 → Al2O3 + ZrO2 (1)

[0018] MgAl2O4 + Al2O3 + ZrO2 → Mg 5+x Al 2.4-x Zr 1.7+0.25x O 12 (2)

[0019] The passive oxidation of the aluminum-zirconium alloy in the outer layer of the product consumes a large amount of O2 in the atmosphere, and the oxygen partial pressure inside the product gradually decreases. Under high temperature and low oxygen partial pressure conditions, the aluminum-zirconium alloy inside the product begins to undergo active oxidation reaction, formula (3), generating Al x O y The gas phase further diffuses to the surface of the product, oxidizes and deposits in the surface layer with high oxygen partial pressure, and further promotes the densification of the product surface.

[0020] Al [AlZr] + O2 → Al x O y (g) (3)

[0021] As the passive oxidation and active oxidation reactions of the aluminum-zirconium alloy in the outer layer of the product proceed, the oxygen partial pressure inside the product gradually decreases to an extremely low value, and the aluminum-zirconium alloy reacts directly with N2 and the residual carbon of the phenolic resin, formula (4), to generate AlN and Al2Zr3C4 in situ; AlN further reacts with MgAl2O4 spinel, formula (5), to generate MgAlON reinforcement phase.

[0022] AlZr + N2 + C → AlN + Al2Zr3C4 (4)

[0023] AlN + MgAl2O4 → MgAlON (5)

[0024] By utilizing the step-by-step change of the reaction mechanism of the aluminum-zirconium alloy from the outside to the inside of the product, a magnesium-aluminum-zirconium composite refractory material with a gradient structure of "dense MgAl2O4-Al2O3-ZrO2 anti-corrosion layer" - "high-strength MgAlON and Al2Zr3C4 co-reinforced MgAl2O4 composite thermal shock resistant zone" is prepared, such as Figure 2 As shown. (Drawings cannot appear in the manual, and drawings can only be placed in the drawings of the manual)

[0025] The present invention also provides a gradient structure magnesium aluminum zirconium composite refractory material, which is obtained by the preparation method of the present invention and has excellent high temperature strength, thermal shock resistance and erosion resistance.

[0026] The present invention innovatively utilizes the sensitive characteristics of aluminum-zirconium alloy to oxygen partial pressure at high temperature, designs in-situ synthesis and cascade reaction paths, and prepares a new type of gradient structure magnesium-aluminum-zirconium composite refractory material, whose outer layer is a dense MgAl2O4-Al2O3-ZrO2 composite material, which can effectively improve the corrosion resistance of the material; its interior is a porous Al2Zr3C4-MgAlON reinforced MgAl2O4 composite material, which can effectively improve the thermal shock resistance of the material. This new type of refractory material with the functional gradient characteristics of "high corrosion resistance working layer-thermal shock resistance internal zone" has broad application prospects in non-ferrous metal smelting furnaces and RH refining furnaces.

[0027] Beneficial effects: In view of the problems in the prior art that it is difficult to balance the corrosion resistance and thermal shock resistance, the present invention utilizes the sensitive characteristics of aluminum-zirconium alloy to oxygen partial pressure at high temperature, designs in-situ synthesis and cascade reaction paths, and prepares a new type of "dense corrosion resistance layer-non-oxide enhanced thermal shock resistance zone" gradient structure magnesium-aluminum-zirconium composite refractory material. The details are as follows:

[0028] (1) The outer layer of the gradient structure magnesium aluminum zirconium composite material is a dense MgAl2O4-Al2O3-ZrO2 composite material with a porosity of ≤5%, which can effectively improve the material's corrosion resistance; its inner layer is a porous Al2Zr3C4-MgAlON reinforced MgAl2O4 composite material with a porosity of 10% to 20%, which can effectively improve the material's thermal shock resistance. This new refractory material with the functional gradient characteristics of "high corrosion resistance working layer-thermal shock resistance internal zone" achieves a synergistic improvement in corrosion resistance and thermal shock resistance, and has broad application prospects in non-ferrous metal smelting furnaces and RH refining furnaces.

[0029] (2) The outer layer of the product is a dense MgAl2O4-Al2O3-ZrO2 composite material, in which the ZrO2 phase is highly uniformly dispersed. On the one hand, the highly finely dispersed active ZrO2 can quickly capture CaO, the main component of the slag, and improve the reaction efficiency of the two, thereby improving the corrosion resistance; on the other hand, the dense structure can greatly reduce the penetration of slag into the interior of the product, thereby improving the corrosion resistance. At the same time, the thickness of the dense layer is about 0.1 to 5 mm. As a working layer, it plays an anti-corrosion function without affecting the thermal shock resistance of the product.

[0030] (3) The interior of the product is a porous Al2Zr3C4-MgAlON reinforced MgAl2O4 composite material. The in-situ synthesized Al2Zr3C4 and MgAlON reinforcement phases have excellent thermal conductivity and low thermal expansion coefficient, which can greatly alleviate the stress concentration caused by temperature gradient and improve the thermal shock resistance of the material.

[0031] (4) The preparation method of the present invention is simple, has high production efficiency, is suitable for industrial production, and has a high pass rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0033] Figure 1 is a flow chart of the preparation method of the present invention;

[0034] Figure 2 It is a schematic diagram of the structure of the material of the present invention. DETAILED DESCRIPTION

[0035] In order to make the invention purpose, technical scheme and beneficial technical effect of the present invention clearer, the present invention is described in detail below in conjunction with specific embodiments. It should be understood that the embodiments described in this specification are only for explaining the present invention, not for limiting the present invention.

[0036] Example 1

[0037] 65wt.% of magnesium aluminum spinel aggregate, 5wt.% of magnesium aluminum spinel fine powder, and 30wt.% of aluminum zirconium alloy fine powder are mixed, and 3wt.% of phenolic resin binder is added to the above mixture, mixed evenly, pressed and molded to obtain a MgAl2O4-AlZr composite body, and dried at 150°C for 24 hours. The dried body is heated to 1350°C at a heating rate of 10°C / min and kept warm for 8 hours to obtain a gradient structure magnesium aluminum zirconium composite refractory material.

[0038] The obtained gradient structure magnesium aluminum zirconium composite refractory material was tested and found that the thickness of the dense layer was about 2mm, the main phase composition of the dense layer was MgAl2O4, Al2O3, ZrO2, and the porosity was 4.0%; the main phase composition of the internal part was MgAl2O4, MgAlON, Al2Zr3C4, and the porosity was 15.2%. The room temperature compressive strength of the product was 216MPa, and the thermal shock resistance (1100℃ water cooling) was ≥25 times.

[0039] Example 2

[0040] 75wt.% of magnesium aluminum spinel aggregate, 5wt.% of magnesium aluminum spinel fine powder, and 20wt.% of aluminum zirconium alloy fine powder are mixed, and 3.5wt.% of phenolic resin binder is added to the above mixture, mixed evenly, pressed and molded to obtain a MgAl2O4-AlZr composite material blank, and dried at 200℃ for 12 hours. The dried blank is heated to 1550℃ at a heating rate of 10℃ / min and kept warm for 5h to obtain a gradient structure magnesium aluminum zirconium composite refractory material.

[0041] The obtained gradient structure magnesium aluminum zirconium composite refractory material was tested and found that the thickness of the dense layer was about 3mm, the main phase composition of the dense layer was MgAl2O4, Al2O3, ZrO2, and the porosity was 3.2%; the main phase composition of the internal part was MgAl2O4, MgAlON, Al2Zr3C4, and the porosity was 14.3%. The room temperature compressive strength of the product was 234MPa, and the thermal shock resistance (1100℃ water cooling) was ≥25 times.

[0042] Example 3

[0043] 90wt.% of magnesium aluminum spinel aggregate, 5wt.% of magnesium aluminum spinel fine powder, and 5wt.% of aluminum zirconium alloy fine powder are mixed, and 3wt.% of phenolic resin binder is added to the above mixture, mixed evenly, pressed and molded to obtain a MgAl2O4-AlZr composite material blank, and dried at 180°C for 15 hours. The dried blank is heated to 1750°C at a heating rate of 10°C / min and kept warm for 3h to obtain a gradient structure magnesium aluminum zirconium composite refractory material.

[0044] The obtained gradient structure magnesium aluminum zirconium composite refractory material was tested and found that the thickness of the dense layer was about 2mm, the main phase composition of the dense layer was MgAl2O4, Al2O3, ZrO2, and the porosity was 4.7%; the main phase composition of the internal part was MgAl2O4, MgAlON, Al2Zr3C4, and the porosity was 16.7%. The room temperature compressive strength of the product was 198MPa, and the thermal shock resistance (1100℃ water cooling) was ≥25 times.

[0045] Example 4

[0046] 80wt.% of magnesium aluminum spinel aggregate, 10wt.% of magnesium aluminum spinel fine powder, and 10wt.% of aluminum zirconium alloy fine powder are mixed, and 3.5wt.% of phenolic resin binder is added to the above mixture, mixed evenly, pressed and molded to obtain a MgAl2O4-AlZr composite material blank, and dried at 180°C for 15 hours. The dried blank is heated to 1750°C at a heating rate of 10°C / min and kept warm for 3h to obtain a gradient structure magnesium aluminum zirconium composite refractory material.

[0047] The obtained gradient structure magnesium aluminum zirconium composite refractory material was tested and found that the thickness of the dense layer was about 2mm, the main phase composition of the dense layer was MgAl2O4, Al2O3, ZrO2, and the porosity was 3.5%; the main phase composition of the internal part was MgAl2O4, MgAlON, Al2Zr3C4, and the porosity was 14.7%. The room temperature compressive strength of the product was 238MPa, and the thermal shock resistance (1100℃ water cooling) was ≥25 times.

[0048] Example 5

[0049] 80wt.% of magnesium aluminum spinel aggregate, 5wt.% of magnesium aluminum spinel fine powder, and 15wt.% of aluminum zirconium alloy fine powder are mixed, and 4wt.% of phenolic resin binder is added to the above mixture, mixed evenly, pressed and molded to obtain a MgAl2O4-AlZr composite material blank, and dried at 180°C for 15 hours. The dried blank is heated to 1750°C at a heating rate of 10°C / min and kept warm for 3h to obtain a gradient structure magnesium aluminum zirconium composite refractory material.

[0050] The obtained gradient structure magnesium aluminum zirconium composite refractory material was tested and found that the thickness of the dense layer was about 2mm, the main phase composition of the dense layer was MgAl2O4, Al2O3, ZrO2, and the porosity was 4.1%; the main phase composition of the internal part was MgAl2O4, MgAlON, Al2Zr3C4, and the porosity was 14.8%. The room temperature compressive strength of the product was 212MPa, and the thermal shock resistance (1100℃ water cooling) was ≥25 times.

[0051] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or substitutions within the technical scope disclosed by the present invention, and these modifications or substitutions should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope determined by the claims.

Claims

1. A magnesium-aluminum-zirconium composite refractory material with a gradient structure, characterized in that: The outer layer is a dense MgAl2O4-Al2O3-ZrO2 composite material with a thickness of 0.1 to 5 mm and a porosity of ≤5%, and the inner layer is a MgAl2O4-MgAlON-Al2Zr3C4-AlZr composite material with a porosity of 10% to 20%.

2. The magnesium-aluminum-zirconium composite refractory material with a gradient structure according to claim 1 is characterized in that: The raw material composition comprises the following mass percentages: 70% to 95% of magnesium-aluminum spinel, 5% to 30% of zirconium-aluminum alloy, and 2% to 5% of phenolic resin binder.

3. The gradient structure magnesium aluminum zirconium composite refractory material according to claim 2 is characterized in that: The magnesium-aluminum spinel raw material includes aggregates with a particle size of 3-1mm and less than 1mm and fine powder with a particle size of ≤0.08mm, wherein the mass percentage of the magnesium-aluminum spinel aggregates with a particle size of 3-1mm and less than 1mm is 65%-90%, and the mass percentage of the magnesium-aluminum spinel fine powder is 5-30%; the zirconium-aluminum alloy raw material is fine powder with a particle size of ≤0.1mm.

4. The gradient structure magnesium aluminum zirconium composite refractory material according to claim 2 or 3, characterized in that: The main chemical components of the zirconium-aluminum alloy raw material are Ti and Al elements. In terms of mass percentage, the content of Zr element is 10% to 50%, and the content of Al element is 50% to 90%.

5. The method for preparing a gradient structure magnesium-aluminum-zirconium composite refractory material according to any one of claims 1 to 4, characterized in that: The steps include: (1) weighing magnesium-aluminum spinel, zirconium-aluminum alloy, and binder according to a ratio, stirring evenly, and making a slurry; (2) placing the clay material in step (1) in a press to form a green body; (3) placing the green body in step (2) in a tunnel kiln and drying it at 150° C. to 200° C. for 12 to 24 hours to reduce the residual moisture to less than 1.5%; (4) The dried bricks are placed in a tunnel kiln and fired at 1350°C to 1750°C in an air atmosphere for 3 to 8 hours.

Citation Information

Patent Citations

  • Magnesium-aluminum-zirconium composite spinel refractory material

    CN102093063A

  • Resin-bonded aluminum-magnesium refractory material

    CN102775171A

  • High-temperature thermal-shock-resistant magnesia alumina spinel-zirconia complex-phase material and preparation method thereof

    CN103496990A

  • Multilayer sintered ceramic body

    EP4032701A1

  • Calcium zirconate / Spinel compound multi porous compact and its manufacturing method

    JP2003073179A

Cited By

  • Gradient-structure metal-oxide-non-oxide composite slide plate and preparation method thereof

    CN121732796A

  • Magnesium aluminate spinel cover plate with compact surface and porous interior for aluminum electrolysis as well as preparation method and application of magnesium aluminate spinel cover plate

    CN121850697A